Penerapan Program Csr Astra Kreatif Oleh Pt Pasangkayu Di Kelurahan Martajaya Kecamatan Pasangkayu Kabupaten Pasangkayu - Haikal Putra Fachrezy; Bahtiar; Adika Tirta Atansyah; Steven Ladjepe; Desinta; Made Serik Ayu; Anisa Auliya; Muzakir Tawil; Rachmad; Richard F. Labiro; abdul rivai (CV. KAMPUS AKADEMIK PUBLISING, 2026)
This study evaluates the implementation of the Astra Kreatif corporate social responsibility (CSR) program carried out by PT Pasangkayu in Martajaya Village, Pasangkayu Subdistrict, Pasangkayu Regency. The objectives are to identify the program activities, assess their socio-economic impacts on the local community, and explore supporting and inhibiting factors in implementation. The study employs a qualitative case study approach with data collected through in-depth interviews with stakeholders (company representatives, village officials, and beneficiaries), participatory observation, and program document analysis. Results indicate that Astra Kreatif focuses on building local entrepreneurial capacity, creative skills training, and provision of small-scale production facilities. Observed positive impacts include improved technical knowledge among participants, increased home-based business opportunities, and strengthened local market networks. However, program effectiveness is constrained by limited sustainable funding, suboptimal inter-institutional coordination, and the need for follow-up to improve access to financing. Recommendations include sustainability planning (micro-financing schemes or market partnerships), enhanced coordination with village government, and regular community-inclusive monitoring and evaluation. These findings inform companies, local policymakers, and researchers on designing more responsive and impactful CSR programs at the community level